Fascicular involvement in common fibular neuropathy: Evaluation with ultrasound. Issue 4 (5th January 2016) - Bignotti, Bianca; Cadoni, Angela; Assini, Andrea; Martinoli, Carlo; Tagliafico, Alberto
ABSTRACT: Introduction: The aim of this study was to demonstrate single fascicular involvement in common fibular (CF) neuropathy using high‐resolution ultrasound (US). Methods: We prospectively enrolled 40 adult patients with clinical and electrodiagnostic suspected CF neuropathy between April 2012 and December 2014. Two musculoskeletal radiologists used high‐resolution US probes to prospectively and independently evaluate the CF nerve bilaterally in these patients. The presence of single fascicular involvement (increased cross‐sectional area and loss of fascicular echotexture) was recorded. Results: US revealed involvement of only 1 fascicular component of the CF nerve in 7 patients. In all these patients, US revealed involvement of the anterior fascicles corresponding to fibers for the deep fibular nerve. Conclusions: High‐resolution US allowed identification of single fascicular involvement in CF neuropathy. Anterior fascicular involvement was present in up to 17% of patients with suspected CF neuropathy. Muscle Nerve 53 : 532–537, 2016